EFFECT OF DIODE LASER 805NM ON THE VIABILITY OF SOME TYPES OF GRAM NEGATIVE AND GRAM POSITIVE PATHOGENIC BACTERIA - Hassan, Layla; Gizar, Rabab; Majeed, Laheeb (Iraqi Journal of Science, 2024)
The effect of diode laser radiation 805nm on the viability of some types of Gram negative and Gram positive pathogenic bacteria (Escherichia coli, Klebsiella pneumonia, Streptococcus pyogenes, Staphylococcus aureus, Salmonella enteritidis and Bacillus cereus) was studied. These types of bacteria were irradiated at 0.94, 2.01 and 2.76 Wat for 1 minute as an exposure time of laser radiation. The results showed that this type of laser radiation had an inhibition action on E. coli, S. pyogene, B. cereus, and S. aureus and a stimulation effect on S. enteritidis and K. pneumonia. In both cases, the effect was dose-dependent.